Design Ideas of Green Energy Market Trading Mechanism Based on Charging Network and Vehicle Network. Issue 5 (February 2019) - Li, Taoyong; Zhang, Jing; Wang, Jiani; Zhang, Yuanxing; Liu, Mi; Jiang, Linru; Liu, Dunnan; Li, Kang
Abstract: The integration and continuous development of vehicle network technology and charging network will provide new ideas for power dispatching and trading, and will also promote the participation of green energy in market transactions. First, this paper combed the development of the charging network and the vehicle network platform, and analyzed the situation of the participation of green energy in the current electricity market. On this basis, combined with the technical characteristics of the charging network and the vehicle network platform, the opportunities and challenges that green energy would face when participating in the market were analyzed. After that, in order to give full play to the technical advantages of the charging network and the network platform of the car, this article put forward two kinds of transaction mechanisms, the direct green energy transaction and the green certificate trading, further evade the market risk, and provide reference for the development of electric vehicles and the development of green energy trading mechanism in China.